Aplikasi Cookpedia Berbasis Android - Clariza Ruth Nugroho; Henry Novianus Palit; Anita Nathania Purbowo (Jurnal Infra, 2018)
Nowadays, the word culinary is currently popular. Many restaurants and cafes were built to fulfill the enthuasism from customers in trying new foods and recipes. Lots of innovation and creativity from the owner were used to attract the customers by creating a new recipe and food. The enthuasism of people in culinary doesn’t stop right there. Their enthuasism leads them to share those food which they ate to the social media so that other people could also know and tried. However, it has limitations and drawbacks because these recipes have not been tested for quality. Not only that, but also many people feels like cooking is difficult because the lack of steps and pictures in a recipe. The lack of steps and pictures in a recipe makes the enthuasism decreasing.Technology is growing rapidly. Many Android developers were started to make an application or software in order to help fulfilling people needs and problems. The technology which are developed nowadays, allows to eliminate the deficiency of a problem. By creating this application, it will help people know which recipe is worth to try depending on the number of likes and comments from the users. Cookpedia also can filter the recipes based on likes so that users can see the recipes which are popular.